(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
there is a lack of River sand and also increment of lots of restrictions on river sand mining and its transportation. For that it becomes necessary to find an alternative for river sand. It is beneficial to find the by product so that its cost is comparatively less and also it can be usable. For that the Copper Slag and waste glass are the best alternatives. By using copper slag and waste glass in concrete we can reduce environmental pollution as well as we can reduce the cost of concrete also. Copper slag and waste glass can possess the physicNowadays al, chemical and mechanical properties that can be used in concrete as a partial replacement for fine aggregates. Copper slag and waste glass is one of the materials that can be considered as a waste material which could have a promising future in the construction industry as a partial or full substitute of any two either cement or aggregates. During the investigations the M30 grades of concrete was prepared and examined at a fresh and hardened stage respectively. Then different mixes were prepared containing 0%, 7.5%, 12.5% and 17.5 % and as partial replacement of fine aggregates with copper slag and 0%, 7.5%, 12.5% and 17.5 % as a partial replacement of fine aggregates with crushed glass waste together in different combinations. The properties which were examined are workability of the different mix by slump test, compressive strength of solidified concrete cube specimens, split tensile strength of solidified cylinder specimens, flexural strength of solidified beam specimens , abrasion test and acid attack as per the IS code Form the results of compressive strength, split tensile strength and flexural strength, the concrete shown higher value at 12.5% replacement of fine aggregate by using copper slag and crushed waste glass on replacement of fine aggregate i.e. sand . We conclude that, by using copper slag and waste glass powder as replacement for fine aggregate in concrete increases the density of concrete. Hence, 12.5 % replacement of copper slag is the optimum proportion for replacing fine aggregate and helps to utilize the waste product in turn helps to protect the environment